AN IMPROVED MATHEMATICAL MODEL OF THE METHOD OF FULLY PREPARING THE DETERMINATION OF FIRING UNITS FOR HITTING THE INFORMATION AND CALCULATION COMPONENT OF THE AUTOMATED FIRE CONTROL SYSTEM OF COMBAT VEHICLES OF REACTIVE ARTILLERY - Majstrenko, O. V.; Makeev, V. I.; Prokopenko, V. V.; Andreiev, І. М.; Kamentsev, S. Y.; Onofriychuk, A. Y. (Radìoelektronika, informatika, upravlìnnâ, 2024)
Context. As part of the automation of the fire control system of rocket artillery combat vehicles, in relation to the preparation of data for firing and fire control, the information and computing process of this system has been improved, namely, the mathematical model of the method of fully preparing the determination of installations for firing projectiles used in rocket salvo fire systems has been improved. In the system of differential equations of the mathematical model of the information and computing process of the component of the automated fire control system of combat vehicles of jet artillery, weighting functions for air temperature, wind influence for the active and passive sections of the projectile flight trajectory and the section of the opening of combat elements have been introduced, which allows determining the weighting coefficients for them for each projectile type. Objective. To improve the information and calculation component of the automated fire control system of combat vehicles of reactive artillery, by improving the mathematical model of the method of full preparation of the determination of installations for firing on damage. Having proposed a system of differential equations that will take into account the weighting functions of air temperature, wind influence for active and passive sections of the projectile flight path and the section of the opening of combat elements, and will also give the opportunity to determine weighting coefficients for each type of projectile based on them, which in turn will lead to an increase the accuracy of determining firing settings. Method. The proposed analytical method allows: to calculate the weighting coefficients for each type of rocket, characterizing the process of the approach of the rocket flight to the tabular trajectory and to set the initial conditions necessary for solving the differential equations of the mathematical model of the information-computing process of the component of the automated fire control system of combat vehicles of rocket artillery; to increase the accuracy of determining firing positions when performing firing tasks, which makes it possible to quickly respond to a change in the combat situation by means of changes in the softwaremathematical process of the automated fire control system; effectively and efficiently ensure the development or clarification of textual and graphic administrative and combat documents based on the results obtained using differential equations of the mathematical model of the information-computational process of the component of the automated fire control system. Results. The improved information and calculation component of the automated fire control system of combat vehicles of jet artillery was tested during the conduct of hostilities. The system of differential equations of the mathematical model of the information-computing process of the component of the automated fire control system of combat vehicles of reactive artillery ensures a timely response to a change in the situation in the information-computational process of the component of the automated fire control system of combat vehicles of reactive artillery during firing and fire control. Provides an opportunity to efficiently and quickly ensure the development or clarification of textual and graphic administrative and combat documents based on the information received during the execution of fire missions. Conclusions. The calculations based on the proposed system of differential equations confirm the improvement of the information-calculation component of the automated fire control system of jet artillery combat vehicles and allow timely response to changes in tasks in the information-calculation process during firing and fire control, as well as effectively and quickly ensure the formation of formalized messages and documents based on the information received during the execution of a fire mission by units of reactive artillery. Prospects for further research are the creation of agreed mathematical methods, models, algorithms and programs for the implementation of the goals and tasks of firing and fire control when compiling Firing Tables for prospective or received combat vehicles of reactive artillery from partners.